Serial yes/no reliability after traumatic brain injury: implications regarding the operational criteria for emergence from the minimally conscious state. Issue 2 (17th January 2008) - Nakase-Richardson, R; Yablon, S A; Sherer, M; Evans, C C; Nick, T G
Abstract : Background: Published guidelines for defining the "minimally conscious state" (MCS) included behaviours that characterise emergence, specifically "reliable and consistent" functional interactive communication (accurate yes/no responding) and functional use of objects. Guidelines were developed by consensus because of the lack of empirical data to guide definitions. Criticism emerged that individuals with severely impaired cognition would have difficulty achieving the requisite threshold of accuracy and consistency proposed to demonstrate emergence from MCS. Objective: To determine the utility of the operational threshold for emergence from post-traumatic MCS, by evaluating a measure of yes/no accuracy (Cognitive Test for Delirium, auditory processing subtest (CTD-AP).) Methods: Prospective, consecutive cohort of responsive patients recovering from traumatic brain injury (TBI), including a subset meeting criteria for MCS at neurorehabilitation admission who improved and were able to undergo the study protocol. Participants were evaluated at least weekly, and given the CTD-AP to assess yes/no responding. Results: Of the 1434 observations from 336 participants, 767 observations yielded inaccurate yes/no responses. 75 participants (22%) never attained consistently accurate yes/no responses at any time during their hospitalisation. Generalised estimating equations analysis revealed that confused participants were more likely to respond inaccurately to yes/no questions. Further, the subset of individuals who were in MCS on rehabilitation admission and improved, were also more likely to respond inaccurately to yes/no questions. Conclusions: Consistent yes/no accuracy is uncommon among responsive patients in early recovery from TBI. These results suggest that the operational threshold for yes/no response accuracy as a diagnostic criterion for emergence from MCS should be revisited.